From fringe to fringe: the shift from the clericalist League of Polish Families to the anticlericalist Palikot Movement 2001-2015 - Zuba, Krzysztof (Religion, state & society, 2017)
The period between 2001 and 2015 brought two events in Poland that deserve to be called phenomena. In 2001 the rightist, clericalist League of Polish Families entered the Sejm. Ten years later, the leftist, anticlericalist Palikot Movement achieved spectacular success in the 2011 elections. These events give a picture of a radical shift in the Polish political scene: a rightist clericalist party disappeared from the right flank of the political scene, while a new, leftist-anticlericalist formation appeared. The article makes reference to a set of five explanations on both the causes and consequences (and permanence) of the observed changes. I argue that only a concurrence of a number of complementary factors - global (secularisation, right-wing populism, postmodernism); structural (changing patterns of rivalry between Polish political parties); and periodic (critical events) - allows us to explain both the radical shift in religious' voting and the success of politically extreme parties. In total, these conditions make up an opportunity structure' within which only a set of mutually conditioning factors can bring about such a critical shift.